A botanical mystery solved by phylogenetic analysis of botanical garden collections: the rediscovery of the presumed-extinct Dracaena umbraculifera. Issue 3 (8th January 2018) - Edwards, Christine E.; Bassüner, Burgund; Birkinshaw, Chris; Camara, Christian; Lehavana, Adolphe; Lowry, Porter P.; Miller, James S.; Wyatt, Andrew; Jackson, Peter Wyse
Abstract: Extinction is the complete loss of a species, but the accuracy of that status depends on the overall information about the species. Dracaena umbraculifera was described in 1797 from a cultivated plant attributed to Mauritius, but repeated surveys failed to relocate it and it was categorized as Extinct on the IUCN Red List. However, several individuals labelled as D. umbraculifera grow in botanical gardens, suggesting that the species' IUCN status may be inaccurate. The goal of this study was to understand (1) where D. umbraculifera originated, (2) which species are its close relatives, (3) whether it is extinct, and (4) the identity of the botanical garden accessions and whether they have conservation value. We sequenced a cpDNA region of Dracaena from Mauritius, botanical garden accessions labelled as D. umbraculifera, and individuals confirmed to be D. umbraculifera based on morphology, one of which is a living plant in a private garden. We included GenBank accessions of Dracaena from Madagascar and other locations and reconstructed the phylogeny using Bayesian and parsimony approaches. Phylogenies indicated that D. umbraculifera is more closely related to Dracaena reflexa from Madagascar than to Mauritian Dracaena . As anecdotal information indicated that the living D. umbraculifera originated from Madagascar, we conducted field expeditions there and located five wild populations; the species' IUCN status should therefore be Critically Endangered because < 50 wild individuals remain. Although the identity of many botanical garden samples remains unresolved, this study highlights the importance of living collections for facilitating new discoveries and the importance of documenting and conserving the flora of Madagascar.